Kyoto Protocol at a dead end? - Friedemann Müller (Stiftung Wissenschaft und Politik (SWP), 2003)
The Kyoto Protocol, the symbol of a global climate protection policy and, since President Bush's brusque termination of U.S. participation in this pact, also a symbol of the rest of the world's ability to act responsibly, is threatening to come to an ignominious end. On 29 September, at the opening ceremony for the World Climate Change Conference, held in Moscow with the support of the United Nations, President Putin buried the hopes of all those who had expected this conference to provide the backdrop for an undertaking by Russia to ratify the Protocol. Without Russia, the Protocol can not enter into force, with Russia's ratification this would be consummated within 90 days, as all other conditions have already been fulfilled. Although Putin has kept all his options open on whether and when to submit the Protocol, originally signed by the YeltsinAdministration, to the Duma for ratification, Russia is already in default with this procedure, and the World Conference offered an ideal opportunity to send an internationally conspicuous signal. This opportunity has been deliberately allowed to slip away.(SWP Comments / SWP)
Keywords: 320